PENGARUH PENGAWASAN TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT ONOLALU KABUPATEN NIAS SELATAN - Yuliana Telaumbanua (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
This study aims to determine the effect of supervision on employee performance in the Onolalu Sub-District Office, South Nias Regency. This type of research is an associative quantitative research. The sample in this study amounted to 30 employees. The analytical method used in this research is simple linear regression analysis. The results of this study indicate that there is a significant influence between supervision and employee performance in the Onolalu District Office, South Nias Regency. In this study, a simple linear regression equation was obtained, namely: Y = 10.072 + 0.777X obtained t count (3.985) > t table (1.701) and a significant level of 0.000 < alpha level 0.05. Then the R Square value of 0.362 or 36.2% of employee performance can be explained by the monitoring variable. Based on the results of this study and the discussion described, it can be concluded that supervision has an effect on employee performance at the Onolalu District Office, South Nias Regency.